Trem2 regulates macrophage phenotype via the JAK2/STAT3 signaling pathway to ameliorate ventricular remodeling after acute myocardial infarction - Zefeng He; Jing Feng; Ru Yan; Peng Wu; Baozhen Zhu; Huifang Li; Taoyu Yang; Yaxin Lu; Baotong He; Xueping Ma; Shaobin Jia; Guangzhi Cong (Molecular Biology Reports, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Acid etching strategy to engineer Fe-doped Bi₂MoO₆ nanosheets with abundant active sites for high-performance photocatalytic antibiotic degradation - Qishe Yan; Linbo Li; Xinyue Chang; Yi Wang; Wenyang Yang; Juncheng Xu; Shaobin Cao (Journal of Environmental Chemical Engineering, 2026)

Triphasic volatile emission dynamics and gene expression in postharvest PGF-lost non-melting peach (Prunus persica) var. RedY - Ping Zhou; Xiaodan Zhang; Xin Feng; Rui Guo; Shaobin Yan; Xiuqing Wei; Liang Li; Yajun Tang; Zhizheng Fang; Yan Lei (Postharvest Biology and Technology, 2026)

Electronic structure modulations of cobalt iron metaphosphate through molybdenum-doping for enhanced and stable oxygen evolution reaction at industrial alkaline condition - Shizhen Bai; Yan Hou; Xueliang Wang; Xuanyi Zhu; Chuang Zhou; Wei Dong; Minghao Li; Shaobin Yang; Erdong Wang (Chemical Engineering Journal, 2026)

Similar mineral-associated organic carbon formation but distinct efficiencies by powdered wollastonite addition between two soils - Yongxue Yan; Liming Yin; Shaobin Yan; Yunting Fang; Ang Wang; Feifei Zhu; Yanfeng Bai; Zhenhua Zhang; Weidong Zhang (Soil Biology and Biochemistry, 2025)

Microbial metabolisms determine soil priming effect induced by organic inputs - Yingyi Fu; Wanling Liu; Zhiyi Chen; Marc Redmile-Gordon; Chao Liang; Caixian Tang; Georg Guggenberger; Shaobin Yan; Liming Yin; Jingjing Peng; Lukas Van Zwieten; Peng Wang; et al. (Soil Biology and Biochemistry, 2025)

Divergent Responses of Soil Positive and Negative Priming Effects to Experimental Warming - Junxia Ding; Yanghui He; Liming Yin; Changjiang Huang; Kui Xue; Shaobin Yan; Ruiqiang Liu; Peng Wang; Xuhui Zhou (Global Ecology and Biogeography, 2025)
Aim The priming effect (PE) refers to changes in the decomposition of native soil organic carbon induced by exogenous carbon inputs. Specifically, an increase in native soil organic carbon decomposition is termed positive PE, whereas a decrease is referred to as negative PE. In this study, we aimed to investigate how positive and negative PE respond to experimental warming and the factors controlling these responses at a global scale. Location Global. Time Period 2008–2025. Major Taxa Studied Soil organic matter priming. Methods We conducted a global meta‐analysis combining 370 paired observations globally and calculated effect sizes ( d ) of experimental warming on soil positive and negative PE separately using the Hedge's d approach. Results Experimental warming induced a significant negative effect on soil PE . Further, positive and negative PE responded differently to increasing temperature: warming decreased positive PE and increased negative PE , lowering the effect size ( d ) of warming on overall PE . Soil pH and clay content had the strongest influence on variance in positive and negative PE under warming, respectively. The effect of warming on PE varied with ecosystem type: positive PE was more strongly inhibited in forests and croplands compared to grasslands, whereas warming significantly decreased the magnitude of negative PE in grasslands. Main Conclusions Our study reveals distinct responses of positive and negative PE to experimental warming, suggesting that PE may be lower under warming, with the effect size ( d ) depending on PE direction and ecosystem type. These findings highlight the importance of distinguishing positive from negative PE to improve predictions of soil organic carbon dynamics under climate warming.

Phytotoxicity of Prussian blue nanoparticles to rice and the related defence mechanisms: In vivo observations and physiological and biochemical analysis - Kai Xu; Yilun Lan; Chenghua Xing; Yuchun Rao; Engao Zhu; Jianfang Yan; Shaobin Wang; Xi-Lin Wu; Miaozhen Cai; Xiaoguang Duan (Chemosphere, 2024)

Drought reduces nitrogen supply and N2O emission in coastal bays - Mingzhen Zhang; Dan Yu; Yiqi Yu; Ruifeng Yan; Yasong Li; Weijie Gong; Kai Xiao; Shaobin Li; Nengwang Chen (Water Research, 2024)

Sodium Selenite Ameliorates Silver Nanoparticles Induced Vascular Endothelial Cytotoxic Injury by Antioxidative Properties and Suppressing Inflammation Through Activating the Nrf2 Signaling Pathway - Yunyun Ma; Lei Wang; Jing He; Xueping Ma; Jingjing Wang; Ru Yan; Wanrui Ma; Huiyan Ma; Yajuan Liu; Hongqian Sun; Xiaoxia Zhang; Shaobin Jia; et al. (Biological Trace Element Research, 2024)
Silver nanoparticles (AgNP) are the dominant nanomaterials in commercial products and the medical field, but the widespread occurrence of AgNP has become a global threat to human health. Growing studies indicate that AgNP exposure can induce vascular endothelial toxicity by excessive oxidative stress and inflammation, which is closely related to cardiovascular disease (CVD), but the potential intrinsic mechanism remains poorly elucidated. Thus, it has been crucial to control the toxicological effects of AgNP in order to improve their safety and increase the outcome of their applications. Multiple researches have demonstrated that sodium selenite (Se) possesses the capability to counteract the toxicity of AgNP, but the functional role of Se in AgNP-induced CVD is largely unexplored. The aim of this study was to explore the potential protective effect of Se on AgNP-induced vascular endothelial lesion and elucidate the underlying mechanisms. An in vivo model of toxicity in animals was established by the instillation of 200 µL of AgNP into the trachea of rats both with (0.2 mg/kg/day) and without Se treated. In vitro experiments, human umbilical vein endothelial cells (HUVECs) were incubated with AgNP (0.3 µg/mL ) and Se for a duration of 24 h. Utilizing transmission electron microscopy, we observed that the internalization of AgNP-induced endothelial cells was desquamated from the internal elastic lamina, the endoplasmic reticulum was dilated, and the medullary vesicle formed. Se treatment reduced the levels of vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1), inhibited the release of pro-inflammatory cytokines (specifically tumor necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6), improved endothelial cell permeability, integrity, and dysfunction, and prevented damage to the aortic endothelium caused by AgNP. Importantly, we found that Se showed the capacity against AgNP with biological functions in guiding the intracellular reactive oxygen species (ROS) scavenging and meanwhile exhibiting anti-inflammation effects. Se supplementation decreased the intracellular ROS release and suppressed NOD-like receptor protein 3 (NLRP3) and nuclear factor kappa-B (NF-κB) mediated inflammation within AgNP-intoxicated rats and HUVECs. The anti-oxidant stress and anti-inflammatory effects of Se were at least partly dependent on nuclear factor erythroid 2-related factor 2 (Nrf2). Overall, our results indicated that the protectiveness of Se against AgNP-induced vascular endothelial toxicity injury was at least attributed to the inhibition of oxidative ROS and pro-inflammatory NF-κB/NLRP3 inflammasome by activating the Nrf2 and antioxidant enzyme (HO-1) signal pathway.

Accelerated screening of active sites on biochar for catalysis and adsorption via multidimensional fingerprint factor descriptors - Wenjie Gao; Ning Li; Zhanjun Cheng; Beibei Yan; Wenchao Peng; Shaobin Wang; Guanyi Chen (Bioresource Technology, 2024)

Construction of propolis flavonoids-phospholipid complex loaded O/W submicron emulsion for enhancing in-vivo dilution stability and gastrointestinal absorption efficiency - Liting Yuan; Yan Zhong; Shaobin Lin; Shufeng Chen; Xiaofang Li; Xiaoming Wang; Fengjian Deng; Wanting Wang; Yusheng Li; Linghao Qin (Journal of Food Engineering, 2024)

Silver nanoparticles induce endothelial cytotoxicity through ROS-mediated mitochondria-lysosome damage and autophagy perturbation: The protective role of N-acetylcysteine - Jing He; Yunyun Ma; Xudong Niu; Jiansheng Pei; Ru Yan; Fangjing Xu; Jing Ma; Xiaojuan Ma; Shaobin Jia; Wanrui Ma (Toxicology, 2024)

Comparative analysis of codon usage patterns in the chloroplast genomes of nine forage legumes - Mingkun Xiao; Xiang Hu; Yaqi Li; Qian Liu; Shaobin Shen; Tailing Jiang; Linhui Zhang; Yingchun Zhou; Yuexian Li; Xin Luo; Lina Bai; Wei Yan (Physiology and Molecular Biology of Plants, 2024)
Leguminosae is one of the three largest families of angiosperms after Compositae and Orchidaceae . It is widely distributed and grows in a variety of environments, including plains, mountains, deserts, forests, grasslands, and even waters where almost all legumes can be found. It is one of the most important sources of starch, protein and oil in the food of mankind and also an important source of high-quality forage material for animals, which has important economic significance. In our study, the codon usage patterns and variation sources of the chloroplast genome of nine important forage legumes were systematically analyzed. Meanwhile, we also constructed a phylogenetic tree based on the whole chloroplast genomes and protein coding sequences of these nine forage legumes. Our results showed that the chloroplast genomes of nine forage legumes end with A/T bases, and seven identical high-frequency (HF) codons were detected among the nine forage legumes. ENC-GC3s mapping, PR2 analysis, and neutral analysis showed that the codon bias of nine forage legumes was influenced by many factors, among which natural selection was the main influencing factor. The codon usage frequency showed that the Nicotiana tabacum and Saccharomyces cerevisiae can be considered as receptors for the exogenous expression of chloroplast genes of these nine forage legumes. The phylogenetic relationships of the chloroplast genomes and protein coding genes were highly similar, and the nine forage legumes were divided into three major clades. Among the clades Melilotus officinalis was more closely related to Medicago sativa , and Galega officinalis was more closely related to Galega orientalis . This study provides a scientific basis for the molecular markers research, species identification and phylogenetic studies of forage legumes.

Synergistic silver doping and N vacancy promoting photocatalytic performances of carbon nitride for pollutant oxidation and hydrogen production - Yifan Kong; Degang Li; Chengxu Zhang; Wenyuan Han; Yan Xue; Weimin Zhang; Hongqi Sun; Shaobin Wang; Xiaoguang Duan (Chemical Engineering Journal, 2024)

Multifunctional biomineralized superhydrophilic coating materials with high transparency and outstanding anti-oil-fouling property for diverse applications - Jianlin Yang; Yan Zhang; Shaobin Yang; Zhecun Wang (Journal of Environmental Chemical Engineering, 2023)

Linking plant traits to rhizosphere priming effects across six grassland species with and without nitrogen fertilization - Jiayu Lu; Liming Yin; Feike A. Dijkstra; Shaobin Yan; Peng Wang; Weixin Cheng (Soil Biology and Biochemistry, 2023)

H2O2 activation and contaminants removal in heterogeneous Fenton-like systems - Ning Li; Xu He; Jingya Ye; Haoxi Dai; Wenchao Peng; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Shaobin Wang (Journal of Hazardous Materials, 2023)

Confinement boosted heterogeneous advanced oxidation processes - Haoxi Dai; Ning Li; Jingya Ye; Jianhui Zhao; Xu He; Xiaoguang Duan; Beibei Yan; Guanyi Chen; Shaobin Wang (Chemical Engineering Journal, 2023)

Conversion and impact of dissolved organic matters in a heterogeneous catalytic peroxymonosulfate system for pollutant degradation - Yanshan Wang; Ning Li; Qinglong Fu; Zhanjun Cheng; Yingjin Song; Beibei Yan; Guanyi Chen; Li'an Hou; Shaobin Wang (Water Research, 2023)

Hazard assessment model of ground subsidence coupling AHP, RS and GIS – A case study of Shanghai - Zhihua Zhang; Shaobin Zhang; Changtao Hu; Xinxiu Zhang; Shuwen Yang; Haowen Yan; Zhen Zhang (Gondwana Research, 2023)

Priming effect on soil carbon decomposition by root exudate surrogates: A meta-analysis - Shaobin Yan; Liming Yin; Feike A. Dijkstra; Peng Wang; Weixin Cheng (Soil Biology and Biochemistry, 2023)

Arbuscular Mycorrhizal Fungi Induced Changes of Pb Migration and Bacterial Community in Both the Rhizosphere and Non-rhizosphere Soils of Paspalum notatum - Zhengjun Feng; Huizhi Ren; Huiping Song; Yan Zou; Miroslav Vosatka; Shaobin Huang; Hainan Lu; Fangqin Cheng (Water, Air, & Soil Pollution, 2023)

Enhanced adsorption of benzo(a)pyrene in soil by porous biochar: Adsorption kinetics, thermodynamics, and mechanisms - Wanjun Wang; Jiaxin Lin; Shaobin Shao; Haojia Chen; Jiawei Dai; Yan Yang (Journal of Environmental Chemical Engineering, 2023)

Fracture evolution during rockburst under true-triaxial loading using acoustic emission monitoring - Shaobin Zhai; Guoshao Su; Shunde Yin; Sizhou Yan; Zhengfu Wang; Liubin Yan (Bulletin of Engineering Geology and the Environment, 2020)

Influence of Radial Stress Gradient on Strainbursts: An Experimental Study - Guoshao Su; Shaobin Zhai; Jianqing Jiang; Gangliang Zhang; Liubin Yan (Rock Mechanics and Rock Engineering, 2017)

Livelihood diversification of farmers and nomads of eastern transect in Tibetan Plateau - Jianzhong Yan; Yingying Wu; Yili Zhang; Shaobin Zhou (Journal of Geographical Sciences, 2010)